Adaptation and validation of the scale for the prevention and control of healthcare—associated infections among nursing students: an exploratory factor analysis approach - Ramos-Meza, Carlos Samuel; Castro-Vargas, Yanet; Chihuantito-Abal, Luis Alberto; Gallegos Aparicio, Edo; Caballero Aparicio, Sdenka; Frisancho-Camero, Miluska; Del Castillo Estrada, Gareth (Frontiers in Public Health, 2025)
This study aimed to adapt and validate the HAInnovPrev scale, a tool for assessing the prevention and control of healthcare-associated infections (HAIs) among nursing students. HAIs are a significant global health concern, particularly in healthcare education, where student training and institutional protocols must align to prevent infections effectively. The development process employed a quantitative approach, utilizing exploratory factor analysis (EFA) on data collected from 347 nursing students across two universities in Peru. This method refined the instrument, reducing the original 15 dimensions to 11 well-defined factors, encompassing key aspects such as institutional compliance, personal motivation, emotional exhaustion, and adherence to hygiene protocols. The results demonstrated that the instrument’s 11-dimensional structure was statistically valid, with measures such as the Kaiser-Meyer-Olkin (KMO) test and Bartlett’s sphericity indicating suitability for factor analysis. Internal consistency reliability, evaluated through omega coefficients, showed strong reliability for most dimensions (ω > 0.70). The findings suggest that the HAInnovPrev scale is a valid and reliable tool to assess critical areas of knowledge, attitudes, and practices regarding HAI prevention among nursing students. Streamlining the scale from 15 to 11 dimensions improves its practical applicability and clarity, focusing on the most relevant factors influencing students’ adherence to infection control practices. Future research should broaden the sample and include observational measures to validate these findings further.